Electrolyte solution, secondary battery, and electric device

By adding imide compounds to the lithium-ion battery electrolyte, the problem of limited solubility of lithium difluorophosphate in carbonate solvents is solved, and the performance of the electrolyte is improved with both high and low temperatures and the performance of lithium-ion secondary batteries at extreme temperatures is achieved.

CN119650851AActive Publication Date: 2025-03-18ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411816942.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, lithium difluorophosphate has limited solubility in carbonate solvents, which limits its low-temperature performance under extreme temperature conditions.

Method used

Imide compounds are added to the electrolyte, and by forming a hydrogen bond and conjugation system within the molecule and intermolecular, the solubility of the lithium salt and the acid rise of the electrolyte are increased, thereby improving the performance of the electrolyte at both high and low temperatures.

Benefits of technology

It effectively improves the low-temperature performance and stability of the electrolyte and enhances the performance of lithium-ion secondary batteries under extreme temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650851A_ABST
    Figure CN119650851A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an electrolyte, a secondary battery and a power utilization device, the electrolyte comprises a solvent, a lithium salt and an additive, the additive comprises a compound shown in the following formula (I): # imgabs0 #, R1 and R2 are substituent groups with the carbon atom number of 1-6, the unsaturation degree of 0-4 and the heteroatom number of 0-3 respectively, and the solvent is a solvent. The heteroatoms are one or more of oxygen, sulfur, nitrogen and phosphorus, and based on the total mass of the electrolyte, the mass fraction of the compound shown in the formula (I) is 0.05%-3%. The compound shown in the formula (I) is an imide compound, has certain alkalinity, and can inhibit acid rise of the electrolyte after being added. Besides, carbonyl groups and imino groups in the annular imide molecules can form intramolecular and intermolecular hydrogen bonds, so that not only is the stability of the molecules increased, but also the ordered arrangement of the molecules can be promoted, the formation of uniform prepolymers is facilitated, the formation of SEI films is further facilitated, and the stability of the electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of batteries, and in particular, to electrolytes, secondary batteries and electrical devices. Background Art

[0002] In the field of new energy, the development of batteries is becoming more and more important, and lithium-ion secondary batteries are a key component in the field of new energy technology industry, which have the advantages of high energy density, high safety and long cycle life. High nickel oxide positive electrode materials are widely used as positive electrode materials for lithium-ion secondary batteries due to their high specific capacity and have broad application prospects. In order to develop in the direction of high energy density battery use demand, silicon negative electrode has become the mainstream of new negative electrode material research due to its high theoretical capacity, good safety performance and wide sources.

[0003] At present, lithium difluorophosphate is a widely used electrolyte additive in lithium-ion batteries, which can improve the energy density and power density of batteries. It also has excellent low-temperature performance and stability, which can extend the battery life. However, the solubility of lithium salts in traditional carbonate systems is poor. This characteristic has become a bottleneck for the full development of its low-temperature performance to a certain extent, limiting its full potential under extreme temperature conditions. Summary of the invention

[0004] The present application effectively suppresses the acid rise of the electrolyte in the later stage and increases the solubility of the lithium salt by adding additives to the electrolyte, thereby achieving the high and low temperature performance of the electrolyte.

[0005] The present application provides an electrolyte, which includes a solvent, a lithium salt and an additive, wherein the additive includes a compound represented by the following formula (I):

[0006]

[0007] Wherein, R1 and R2 are substituents having 1-6 carbon atoms, 0-4 unsaturations, and 0-3 heteroatoms, respectively, and the heteroatoms are one or more of oxygen, sulfur, nitrogen, and phosphorus, and based on the total mass of the electrolyte, the mass fraction of the compound shown in formula (I) is 0.05%-3%, optionally, 0.1%-0.5%. As can be seen from the above, the compound shown in formula (I) in the additive is an imide compound, which has a certain alkalinity and can inhibit the acid rise of the electrolyte after addition. In addition, the carbonyl and imino groups in the cyclic imide molecules can form intramolecular and intermolecular hydrogen bonds, which not only increase the stability of the molecules, but also promote the orderly arrangement of the molecules, which is conducive to the formation of a uniform prepolymer, and then conducive to the formation of a SEI (negative electrode-electrolyte interface) film, thereby improving the stability of the electrolyte.

[0008] In some embodiments, R1 and R2 are each an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group, or a heterocyclic substituent.

[0009] In some embodiments, the compound represented by the above formula (I) has the following structure:

[0010]

[0011]

[0012] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the lithium salt is 12%-16%. Further, the lithium salt further includes lithium difluorophosphate (LiPO2F2), and the mass fraction of lithium difluorophosphate is 0.5%-1% based on the total mass of the electrolyte. Specifically, lithium difluorophosphate is a widely used electrolyte lithium salt additive in lithium-ion secondary batteries, which can improve the energy density and power density of the battery, and also has excellent low-temperature performance and stability, which can extend the battery life. In addition, as a lithium salt additive with positive and negative electrode film-forming ability, it significantly reduces the impedance level of the secondary battery, thereby enhancing the overall performance of the secondary battery while particularly improving the performance of the secondary battery in a low temperature environment. However, it is worth noting that due to the relatively limited solubility of lithium difluorophosphate in carbonate solvents, this feature has become a bottleneck for the full development of its low-temperature performance to a certain extent, limiting its full potential under extreme temperature conditions. In the present application, the compound represented by formula (I) in the additive is an imide structure, and the unshared electron pair on the amino nitrogen in the molecule forms a conjugated system with the π electrons of the carbonyl group, which reduces the electron cloud density on the nitrogen, thereby weakening the ability to accept protons, and the CN bond has a certain degree of double bond. However, the electron cloud density on the nitrogen is reduced, which increases the polarity of the NH bond. Therefore, the additive of the compound represented by formula (I) provided in the present application can assist the dissolution of the lithium salt additive of lithium difluorophosphate, thereby improving the low temperature performance.

[0013] In some embodiments, the solvent includes one or more of carbonates, carboxylates, ethers, and nitriles.

[0014] In some specific embodiments, the additive further includes one or more of fluoroethylene carbonate, propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), etc. Specifically, fluoroethylene carbonate, propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), etc. can improve the stability and safety of the battery, reduce the side reactions of the battery during the charge and discharge process, and thus improve the overall performance of the battery.

[0015] Some embodiments of the present application also provide a secondary battery, comprising: a positive electrode, a negative electrode, and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the above electrolyte. Other embodiments of the present application also provide an electrical device including the secondary battery.

[0016] In summary, the electrolyte provided by the present application effectively suppresses the acid rise of the electrolyte in the later stage and improves the high and low temperature performance of the electrolyte. DETAILED DESCRIPTION

[0017] In the field of new energy, the development of secondary batteries has become increasingly important. The present application provides an electrolyte, which includes a solvent, a lithium salt and an additive, wherein the additive includes a compound represented by the following formula (I):

[0018]

[0019] Wherein, R1 and R2 are substituents with 1-6 carbon atoms, 0-4 unsaturation, and 0-3 heteroatoms, respectively, and the heteroatoms are one or more of oxygen, sulfur, nitrogen, and phosphorus, and based on the total mass of the electrolyte, the mass fraction of the compound shown in formula (I) is 0.05%-3%, and optionally, 0.1%-0.5%. As can be seen from the above, the compound imide compound shown in formula (I) has a certain alkalinity, and can suppress the acid rise of the electrolyte after addition. In addition, the carbonyl group and imino group in the cyclic imide molecule can form intramolecular and intermolecular hydrogen bonds, which not only increases the stability of the molecule, but also promotes the orderly arrangement of the molecules, which is conducive to the formation of a uniform prepolymer, and then conducive to the formation of a SEI (negative electrode-electrolyte interface) film, thereby improving the stability of the electrolyte.

[0020] In some embodiments, R1 and R2 are each an alkyl group, an alkenyl group, an alkynyl group, a carbonyl group, an ester group, an amino group, or a heterocyclic substituent.

[0021] In some embodiments, the compound represented by formula (I) is the following structure:

[0022]

[0023] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the lithium salt is 12%-16%. Specifically, the lithium salt may include one or more of lithium hexafluorophosphate, lithium bis(trifluoromethyl)sulfonyl imide, lithium bis(trifluoromethyl)sulfonyl imide, lithium acetate, lithium methane sulfonate, lithium trifluoromethyl sulfonate, etc. The lithium salt may be a single lithium salt or a mixed lithium salt, for example, the mass ratio of lithium hexafluorophosphate: lithium bis(trifluoromethyl)sulfonyl imide = 14:1 / 14:2 / 13:2, etc.

[0024] Further, the additive also includes lithium difluorophosphate (LiPO2F2), and the mass fraction of lithium difluorophosphate is 0.5%-1% based on the total mass of the electrolyte. Specifically, lithium difluorophosphate is a widely used electrolyte lithium salt additive in lithium ion secondary batteries, which can improve the energy density and power density of the battery, and also has excellent low temperature performance and stability, which can extend the battery life. In addition, as a lithium salt additive with positive and negative electrode film forming ability, the impedance level of the secondary battery is significantly reduced, thereby enhancing the overall performance of the secondary battery, and particularly improving the performance of the secondary battery in a low temperature environment. However, it is worth noting that due to the relatively limited solubility of lithium difluorophosphate in carbonate solvents, this characteristic has become a bottleneck for the full play of its low temperature performance to a certain extent, limiting its potential under extreme temperature conditions. In the present application, the compound shown in formula (I) is an imide structure, and the unshared electron pair on the amino nitrogen in the molecule forms a conjugated system with the π electrons of the carbonyl group, which reduces the electron cloud density on the nitrogen, thereby weakening the ability to accept protons, and then the CN bond has a certain degree of double bond. However, the electron cloud density on nitrogen decreases, which increases the polarity of the NH bond. Therefore, the compound represented by formula (I) provided in the present application can assist in the dissolution of the lithium salt additive of lithium difluorophosphate (LiPO2F2), thereby improving the low-temperature performance.

[0025] In some embodiments, the solvent includes one or more of carbonates, carboxylates, ethers and nitriles. Specifically, the solvent can be one or more of carbonates (ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, fluoroethylene carbonate), carboxylates (ethyl formate, ethyl acetate, propyl acetate, ethyl propionate), ethers (ethylene glycol dimethyl ether, diethanol diethyl ether), nitriles (acetonitrile, propionitrile, butyronitrile, valeronitrile), and the mass fraction of the solvent is between 70% and 80% based on the total mass of the electrolyte.

[0026] In some specific embodiments, the additives further include fluoroethylene carbonate, propenyl-1,3-sultone (PST) and tetravinylsilane (TVSI). In some embodiments, based on the total mass of the electrolyte, the mass fraction of fluoroethylene carbonate, propenyl-1,3-sultone (PST) and tetravinylsilane (TVSI) is less than or equal to 3%. Specifically, fluoroethylene carbonate, propenyl-1,3-sultone (PST) and tetravinylsilane (TVSI) can improve the stability and safety of the battery, reduce the side reactions of the battery during the charge and discharge process, and thus improve the overall performance of the battery.

[0027] Some embodiments of the present application also provide a secondary battery, including: a positive electrode, a negative electrode, and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the above-mentioned electrolyte. Other embodiments of the present application also provide an electrical device including the secondary battery. In one embodiment, the secondary battery is a lithium-ion secondary battery. Specifically, the secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The specific structure of the secondary battery is described in detail below:

[0028] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the surface of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive electrode current collector is, for example, 8μm to 15μm. In this embodiment, the positive electrode current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive electrode current collector has two oppositely disposed surfaces along its own thickness direction, and the positive electrode active material layer can be disposed on the surface of any one side thereof, or on both surfaces. The positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder, wherein the positive electrode active material includes but is not limited to one or more of lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA). In some embodiments, the conductive agent and the binder are not specifically limited, and those skilled in the art can select according to actual needs.

[0029] As an example, the positive electrode binder is selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The positive electrode conductive agent is selected from one or at least two of conductive carbon black (Super P), acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode active material layer can be set according to the conventional settings in the art.

[0030] The negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a thickener. The negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the thickener can be selected from conventional materials in the art, and no specific restrictions are made here.

[0031] As an example, the negative electrode material is selected from carbon and / or silicon negative electrode materials, wherein the carbon negative electrode material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; the silicon negative electrode material is such as elemental silicon, silicon oxide compounds, silicon carbon compounds, etc. (silicon oxide or silicon carbon system). The negative electrode conductive agent is selected from one or a combination of two or more of conductive carbon black, nano silver powder, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR) or a combination of multiple compositions mixed in any proportion; the thickener can be sodium carboxymethyl cellulose (CMC-Na).

[0032] The separator is set between the positive electrode and the negative electrode to play a role of isolation. The separator can be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the separator is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0033] The electrolyte infiltrates the positive electrode and the negative electrode. During the charge and discharge process of the battery, lithium ions are inserted and removed back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting lithium ions. The electrolyte provided in this application is selected as the electrolyte.

[0034] The preparation process of lithium-ion secondary batteries is described below:

[0035] (1) Preparation of positive electrode

[0036] The positive electrode material, positive electrode conductive agent and positive electrode binder are mixed in a certain mass ratio, and then the solvent N-methylpyrrolidone (NMP) is added in batches under high-speed stirring and stirred evenly to obtain a positive electrode slurry with a certain viscosity; the positive electrode slurry is then evenly coated on the positive electrode current collector aluminum foil, and the positive electrode is obtained after drying, rolling and slitting.

[0037] (2) Preparation of negative electrode

[0038] The above-mentioned negative electrode active material, negative electrode conductive agent, negative electrode binder and thickener are mixed in proportion, deionized water is added and stirred evenly under the stirring action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for drying, and cold pressed and cut to obtain a negative electrode.

[0039] (3) Preparation of electrolyte

[0040] In an argon atmosphere glove box with a water content of <10 ppm, fully dried lithium salt and additives are dissolved in an organic solvent and mixed evenly to obtain an electrolyte.

[0041] (4) Preparation of diaphragm

[0042] A 12 μm thick polypropylene (PP) or polyethylene (PE) porous polymer film is selected.

[0043] (5) Assembly of secondary batteries:

[0044] The positive electrode, separator and negative electrode prepared above are stacked or wound in sequence to form a bare battery cell; then wrapped with aluminum plastic film, transferred to a vacuum drying oven and dried at 120°C, sealed after injecting electrolyte, and the electrolyte is formed to finally prepare a soft-pack battery (i.e., a lithium-ion secondary battery).

[0045] Those skilled in the art will understand that the above-described method for preparing a lithium-ion secondary battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0046] The reagents and raw materials used in the present invention are commercially available.

[0047] The secondary battery can be applied to any suitable electrical device, including but not limited to electric vehicles.

[0048] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0049] Example 1

[0050] (1) Preparation of positive electrode:

[0051] Nickel cobalt manganese oxide (LiNi 0.9 Co 0.05 Mn 0.05 O2), polyvinylidene fluoride as a binder and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the system is stirred under the action of a vacuum mixer until it becomes uniform and transparent to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then the aluminum foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the positive electrode (pole sheet).

[0052] (2) Preparation of negative electrode:

[0053] 90% by mass of artificial graphite, 10% by mass of silicon-carbon composite material as negative electrode active materials, Super P as a conductive agent, sodium carboxymethyl cellulose (CMC-Na) as a thickener, and styrene-butadiene rubber (SBR) as a binder are mixed in a mass ratio of 96:1:1:2, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil. After that, the copper foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode (pole sheet).

[0054] (3) Preparation of electrolyte:

[0055] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 3:5:2 to form an organic solvent at a ratio of 70%-80% of the total mass of the electrolyte. Then lithium salts and additives are added and mixed evenly to obtain an electrolyte (i.e., Example 1 in Table 1 below). Specifically, the lithium salt includes lithium hexafluorophosphate and lithium bisfluorosulfonyl imide, and the mass fractions of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide relative to the total amount of the electrolyte are 14% and 1%. The additive includes compound 1 and lithium difluorophosphate (LiPO2F2). Specifically, lithium difluorophosphate (LiPO2F2) accounts for 0.5% of the total mass of the electrolyte as a lithium salt additive. Further, based on the total mass of the electrolyte, the mass fraction of compound 1 is 0.3%, and compound 1 has the following structure:

[0056]

[0057] (4) Preparation of diaphragm:

[0058] Polypropylene (PP) with a thickness of 12 μm was selected as the separator.

[0059] (5) Preparation of secondary batteries:

[0060] The positive electrode, separator and negative electrode prepared above are stacked or wound in sequence to form a bare battery cell; then the battery cell is wrapped with aluminum plastic film, transferred to a vacuum drying oven and dried at 120°C, sealed after injecting electrolyte, and the electrolyte is formed to finally prepare a soft pack battery (i.e., a lithium ion secondary battery)

[0061] Example 2

[0062] The preparation method is consistent with that of Example 1, except that in Example 2, compound 1 is replaced by compound 2 having the following structure:

[0063]

[0064] Example 3

[0065] The preparation method is consistent with that of Example 1, except that in Example 3, compound 1 is replaced by compound 3 having the following structure:

[0066]

[0067] Example 4

[0068] The preparation method is consistent with that of Example 1, except that in Example 4, compound 1 is replaced by compound 4 having the following structure:

[0069]

[0070] Example 5

[0071] The preparation method is consistent with that of Example 1, except that in Example 5, the mass fraction of lithium difluorophosphate (LiPO2F2) is 1% based on the total mass of the electrolyte.

[0072] Example 6

[0073] The preparation method is consistent with that of Example 1, except that in Example 6, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 1%.

[0074] Example 7

[0075] The preparation method is consistent with that of Example 1, except that in Example 7, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 3%.

[0076] Example 8

[0077] The preparation method is consistent with that of Example 1, except that in Example 8, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 0.05%.

[0078] Example 9

[0079] The preparation method is consistent with that of Example 1, except that in Example 9, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 3.5%.

[0080] Example 10

[0081] The preparation method is consistent with that of Example 1, except that in Example 10, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 0.1%.

[0082] Embodiment 11

[0083] The preparation method is consistent with that of Example 1, except that in Example 11, based on the total mass of the electrolyte, the mass fraction of Compound 1 is 0.5%.

[0084] Example 12

[0085] The preparation method is consistent with that of Example 1, except that the additive of the electrolyte of Example 12 further includes 2.5% by weight of fluoroethylene carbonate.

[0086] Embodiment 13

[0087] The preparation method is consistent with that of Example 12, except that the additive of Example 13 further includes 0.2% of propenyl-1,3-sultone (PST) and 0.3% of tetravinylsilane (TVSI).

[0088] Embodiment 14

[0089] The preparation method is consistent with that of Example 1, except that lithium difluorophosphate (LiPO2F2) is not added in Example 12.

[0090] Comparative Example 1

[0091] The preparation method is consistent with that of Example 1, except that Compound 1 and lithium difluorophosphate (LiPO2F2) are not added in Comparative Example 1.

[0092] Comparative Example 2

[0093] The preparation method is consistent with that of Example 1, except that in Comparative Example 2, Compound 1 is not added.

[0094] The secondary batteries in the above-mentioned Examples 1-14 and Comparative Examples 1-2 can be tested by the following method:

[0095] (1) Impedance DCR at -20℃:

[0096] The temperature of the thermostat was adjusted to -20°C, and the secondary batteries in the above embodiments 1-14 and comparative examples 1-2 were allowed to stand for 2h, charged at 0.33C constant current to 4.25V, then charged at 4.25V constant voltage to 0.05C cutoff, allowed to stand for 30min, and then discharged at 0.33C constant current to 2.5V; 0.33C charge and discharge cycle was performed twice, and the last discharge capacity was recorded as C0; after standing for 30min, 0.33C was discharged to 50% C0, the battery cell SOC was adjusted to 50%, allowed to stand for 30min, the static terminal voltage V1 was recorded, C0 constant current discharge was performed for 30s, the terminal voltage V2 and current I were recorded, and DCR = (V1-V2) / I was calculated.

[0097] (2) Capacity recovery rate after 30 days of storage at 60°C:

[0098] At 25°C, the secondary batteries in the above Examples 1-14 and Comparative Examples 1-2 were charged to 4.25V at a constant current of 0.33C, and then charged to a current of 0.05C at a constant voltage, and allowed to stand for 30 minutes. After repeating 2-3 times, the last 0.33C discharge capacity C1 was recorded. The fully charged battery was then placed in a 60°C oven for storage for 30 days, the battery core was cooled, the oven temperature was adjusted to 25°C, allowed to stand for 10 minutes, and discharged to 2.5V at a constant current of 0.33C, followed by 0.33C rate charge and discharge, 2.5V-4.25V voltage range, and after 2 cycles, the last discharge capacity C2 was recorded. The capacity recovery rate of the secondary battery relative to that before storage was calculated according to the following formula:

[0099] Capacity recovery rate (%) = (C2 / C1) × 100%

[0100] The test results are shown in Table 1 below.

[0101] Table 1. Secondary battery performance test results in Examples 1-14 and Comparative Examples 1-2

[0102]

[0103]

[0104] It can be seen from the above examples 1-4 that the additive in the electrolyte includes a compound represented by the following formula (I):

[0105]

[0106] Wherein, R1 and R2 are substituents having 1-6 carbon atoms, 0-4 unsaturation, and 0-3 heteroatoms, respectively, and the heteroatoms are one or more of oxygen, sulfur, nitrogen, and phosphorus. As can be seen from the above, the compound shown in formula (I) is an imide compound, which has a certain alkalinity and can suppress the acid rise of the electrolyte after addition. In addition, the carbonyl group and imino group in the cyclic imide molecule can form intramolecular and intermolecular hydrogen bonds, which not only increases the stability of the molecule, but also promotes the orderly arrangement of the molecules, is conducive to the formation of a uniform prepolymer, and then forms a SEI (negative electrode-electrolyte interface) film, thereby improving the performance of the electrolyte.

[0107] It can be seen from Examples 1-4 that for different compounds represented by formula (I) (Compounds 1 to 4), there are some differences in the impedance at -20°C and the performance of HTS, but the differences are limited and all can improve the performance of the electrolyte.

[0108] From the comparison of Examples 1-11 and Example 9, it can be seen that, based on the total mass of the electrolyte, the mass fraction of the compound represented by formula (I) is better when it is 0.05%-3%, and the performance is better when it is 0.1%-0.5%. When the mass fraction of the compound represented by formula (I) is too large, the SEI film thickness will increase, the impedance of the entire battery cell will deteriorate, and its dynamics will be affected.

[0109] As can be seen from Examples 1 and 5, based on the total mass of the electrolyte, the mass fraction of lithium difluorophosphate (LiPO2F2) is preferably 0.5%-1%. Lithium difluorophosphate is a widely used electrolyte lithium salt additive in lithium-ion secondary batteries, which can improve the energy density and power density of the battery. It also has excellent low-temperature performance and stability, and can extend the battery life. In addition, as a lithium salt additive with positive and negative electrode film-forming ability, it significantly reduces the impedance level of the secondary battery, thereby enhancing the overall performance of the secondary battery while particularly improving the performance of the secondary battery in a low-temperature environment. However, due to the relatively limited solubility of lithium difluorophosphate in carbonate solvents, this feature has become a bottleneck for the full development of its low-temperature performance to a certain extent, limiting its full potential under extreme temperature conditions. Therefore, when its mass fraction is large, it will affect the performance of the electrolyte.

[0110] It can be seen from Examples 12 to 13 that the additives may also include FEC, PST, TVSI, etc., which may further improve the stability of the electrolyte.

[0111] As can be seen from Example 14 and Comparative Example 3, the compound shown in formula (I) in the additive and lithium difluorophosphate (LiPO2F2) are used together for a better effect. Therefore, in the present application, the compound shown in the above formula (I) is an imide structure, and the unshared electron pair on the amino nitrogen in the molecule forms a conjugated system with the π electrons of the carbonyl group, which reduces the electron cloud density on the nitrogen, thereby weakening the ability to accept protons, and then the CN bond has a certain degree of double bond. However, the electron cloud density on the nitrogen is reduced, so that the polarity of the NH bond is increased, and therefore, the compound shown in formula (I) provided in the present application can assist the dissolution of the lithium salt additive of lithium difluorophosphate (LiPO2F2), thereby improving the low temperature performance. In addition, if only lithium difluorophosphate (LiPO2F2) is used, the electrolyte will not achieve a good effect.

[0112] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. An electrolyte, characterized in that: It includes a solvent, a lithium salt and an additive, wherein the additive includes a compound represented by the following formula (I): Wherein, R1 and R2 are substituents having 1-6 carbon atoms, 0-4 unsaturations, and 0-3 heteroatoms, respectively, and the heteroatoms are one or more of oxygen, sulfur, nitrogen, and phosphorus, and based on the total mass of the electrolyte, the mass fraction of the compound represented by formula (I) is 0.05%-3%.

2. The electrolyte according to claim 1, characterized in that The R1 and R2 are respectively alkyl, alkenyl, alkynyl, carbonyl, ester, amino or heterocyclic substituents.

3. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass fraction of the compound represented by formula (I) is 0.1%-0.5%.

4. The electrolyte according to claim 2, characterized in that The compound represented by the formula (I) has the following structure:

5. The electrolyte according to claim 1, characterized in that The additive further comprises lithium difluorophosphate, and the mass fraction of the lithium difluorophosphate is 0.5%-1% based on the total mass of the electrolyte.

6. The electrolyte according to claim 1, characterized in that The solvent includes one or more of carbonates, carboxylates, ethers and nitriles. Based on the total mass of the electrolyte, the mass fraction of the solvent is 70%-80%.

7. The electrolyte according to claim 1, characterized in that The additive further comprises one or more of fluoroethylene carbonate, propenyl-1,3-sultone and tetravinylsilane.

8. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the additive includes 0.3% of the compound represented by formula (I) and 0.5% of lithium difluorophosphate.

9. A secondary battery, characterized in that: include: A positive electrode, a negative electrode and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the electrolyte according to any one of claims 1-9.

10. An electrical device, characterized in that: The secondary battery according to claim 10 is included.

Citation Information

Patent Citations

  • Novel lithium salt additive and non-aqueous electrolyte for lithium-ion batteries

    CN110299562A

  • Electrolyte, secondary battery, and electric device

    CN115149102A

  • Novel additive, electrolyte and lithium ion battery

    CN117996188A

  • Non-aqueous electrolyte and secondary battery

    CN118281330A

  • Electrolyte additive, non-aqueous electrolyte, lithium ion battery, battery module, battery pack and electric device

    CN118867393A